Sequential Search Algorithm Implementation on Web-Based EDocument Search Application - Diana Diana; Yozi Dwi Putra (Universitas Negeri Medan, 2022)
Technological developments have entered the era of the Industrial Revolution 4.0. The Industrial Revolution 4.0 is called the digital era. One of the keys that must be improved in this era is the ability to manage data that is safe and precise in accordance with applicable regulations. The first step taken in managing documents is converting the document into an e-document and saving it to an application. The e-document application that was built is a web-based application because of the ease in accessing e-documents, it can be done anywhere and anytime via internet access. Search is a fundamental process in processing large amounts of data. Search requires an algorithm. The sequential search algorithm is the simplest search model performed on a data set. The test results on the application show that the e-document application can run well on the web, the source code in the application and the sequential search algorithm logic path in the application are declared valid, and the data search process finds results that match the keywords.